x-5-7=2(x+2)

Simple and best practice solution for x-5-7=2(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-5-7=2(x+2) equation:


Simplifying
x + -5 + -7 = 2(x + 2)

Reorder the terms:
-5 + -7 + x = 2(x + 2)

Combine like terms: -5 + -7 = -12
-12 + x = 2(x + 2)

Reorder the terms:
-12 + x = 2(2 + x)
-12 + x = (2 * 2 + x * 2)
-12 + x = (4 + 2x)

Solving
-12 + x = 4 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-12 + x + -2x = 4 + 2x + -2x

Combine like terms: x + -2x = -1x
-12 + -1x = 4 + 2x + -2x

Combine like terms: 2x + -2x = 0
-12 + -1x = 4 + 0
-12 + -1x = 4

Add '12' to each side of the equation.
-12 + 12 + -1x = 4 + 12

Combine like terms: -12 + 12 = 0
0 + -1x = 4 + 12
-1x = 4 + 12

Combine like terms: 4 + 12 = 16
-1x = 16

Divide each side by '-1'.
x = -16

Simplifying
x = -16

See similar equations:

| 12(x-3)-32=5(13+x) | | 92+53+115+2x+3x=540 | | 0=7/6x+6 | | 2(-8+6x)=-4 | | 2(5x+7)=-42+26 | | 5(-6x+3)=15 | | 1x-3=-4x+37 | | 1=7/6x+6 | | -1(5x-3)=1 | | 2x+42=-4x | | -5x+6-x=-6 | | 2x-8=-3x+22 | | 6x+7(2-x)=14-9x-8 | | Y=7/6(0)+6 | | 3x-9=-4x+19 | | 1x-4=-4x+36 | | 3(x+5)(x-10)=7 | | 79-17/8 | | 8=-3x+4x+1 | | 3(c-5)+4c(c-5)= | | 11x-7x=4 | | 3(x-4)=2(5x-11) | | 6x-3(1)=0 | | -7x-9=54 | | 4x+48=-2x | | 5x-15=-2x+20 | | 2x-6=-4x+42 | | x=5::3:2.5 | | 6(0)-3y=0 | | 4x-12=-4x+28 | | 3/2m-m=41/2m | | 10x+5x+45+90=360 |

Equations solver categories